Faktor-Faktor yang Mempengaruhi Kejadian Hipertensi pada Lansia di Desa Sei Rotan Kecamatan Percut Sei Tuan - Khairi Rizky Handayani; Putri Athika Maulana; Ingke Siti Hazun; Khairunnisa Khairunnisa; Nindy Rahmalila Putri; Susilawati Susilawati (Universitas Batanghari Jambi, 2023)
Hypertension is often called the silent killer. Because hypertension is a deadly disease but is not accompanied by symptoms. Hypertension occurs when the systolic pressure is 140 mmHg or the diastolic pressure is 90 mmHg. This study aims to determine what factors influence the incidence of hypertension in the elderly in Sei Rotan Village, Percut Sei Tuan District. This research is a quantitative descriptive study with a cross sectional research design approach. The results showed that the factors affecting hypertension in the elderly in Sei Rotan Village, Percut Sei Tuan District, were gender, age, education, and lifestyle. Suggestions from this study are that village health cadres should revive one of the preventions of hypertension in the elderly, namely elderly exercise and for the family to pay more attention to food intake patterns for families, especially the elderly.